Resposta inflamatória à abordagem laparoscópica da peritonite induzida em ratos: comparação do pneumoperotônio realizado com CO² ou gás hélio - Paulo Roberto Rodrigues Bicalho (2017)
Background: peritonitis is inflammation of the secondary peritoneum of a heterogeneous group of conditions very common in surgical practice whose severity varies from mild infections to catastrophic. The laparoscopic approach to this condition has been successfully employed. Data from the literature suggest that the type of gas used to perform the pneumoperitoneum can affect the local and systemic inflammatory response. Objective: Verify local inflammation and the systemic immune response in rats submitted to laparoscopic cecal ligation and puncture (CLP) using helium or CO2. Method: Male Wistar rats were randomly assigned to four groups. In the PC group (n = 8), peritonitis was induced and a laparoscopic method was performed using CO2. In the CC group (n = 8), we performed simulated surgery and the laparoscopic method using CO2. In the PH group (n = 8), peritonitis was induced and the laparoscopic approach was performed using Helium. In the CH group (n = 8), a simulated surgery was performed and the laparoscopic approach was performed using Helium. All animals were treated with saline lavage and a systemic antibiotic was used. After 24 hours the abdominal cavity was accessed for macro and microscopic analysis, blood was collected for leucometria and dosage of cortisol, interleukin IL-1, IL-6 and tumor necrosis factor alpha (TNF) and the animals were killed by overdose. Data were compared between the groups by qui-quadrado and Student's T test, considered differences p <0.05. Results: Residual abscess wasn´t observed at macroscopy. Adhesions were present in all groups without significant difference. There was also no difference in microscopy between groups, such as angiogenesis, mesothelial cell edema, fibrinous exudate, presence of microabcesses and macrophage/fibroblast (M/F) ratio. The serum concentration of cortisol and TNF was not different between the groups (p=0.17 and 0.18, respectively). The concentration of IL-1 was higher in the groups with peritonitis in which CO2 (CC) or helium (PH) comparing to the groups without peritonitis (p<0.001) but without difference between them (p=1,0). A similar result was observed in the serum concentration of IL-6. Conclusion: The local inflammation and systemic immune response in rats submitted to cecal ligation and puncture (CLP) and treated by laparoscopy with CO2 or helium insufflation showed no difference.